Alterations of red cell membrane properties in neuroacanthocytosis. - Claudia Siegl; Patricia Hamminger; Herbert Jank; Uwe Ahting; Benedikt Bader; Adrian Danek; Allison Gregory; Monika Hartig; Susan Hayflick; Andreas Hermann; Holger Prokisch; Esther M Sammler; et al. (PLoS ONE)
Neuroacanthocytosis (NA) refers to a group of heterogenous, rare genetic disorders, namely chorea acanthocytosis (ChAc), McLeod syndrome (MLS), Huntington's disease-like 2 (HDL2) and pantothenate kinase associated neurodegeneration (PKAN), that mainly affect the basal ganglia and are associated with similar neurological symptoms. PKAN is also assigned to a group of rare neurodegenerative diseases, known as NBIA (neurodegeneration with brain iron accumulation), associated with iron accumulation in the basal ganglia and progressive movement disorder. Acanthocytosis, the occurrence of misshaped erythrocytes with thorny protrusions, is frequently observed in ChAc and MLS patients but less prevalent in PKAN (about 10%) and HDL2 patients. The pathological factors that lead to the formation of the acanthocytic red blood cell shape are currently unknown. The aim of this study was to determine whether NA/NBIA acanthocytes differ in their functionality from normal erythrocytes. Several flow-cytometry-based assays were applied to test the physiological responses of the plasma membrane, namely drug-induced endocytosis, phosphatidylserine exposure and calcium uptake upon treatment with lysophosphatidic acid. ChAc red cell samples clearly showed a reduced response in drug-induced endovesiculation, lysophosphatidic acid-induced phosphatidylserine exposure, and calcium uptake. Impaired responses were also observed in acanthocyte-positive NBIA (PKAN) red cells but not in patient cells without shape abnormalities. These data suggest an "acanthocytic state" of the red cell where alterations in functional and interdependent membrane properties arise together with an acanthocytic cell shape. Further elucidation of the aberrant molecular mechanisms that cause this acanthocytic state may possibly help to evaluate the pathological pathways leading to neurodegeneration.